144 Bradycardia support in the district general hospital—development of a new protocol for managing bradycardia by the non-cardiologist. (22nd September 2015) - Elder, D H J; Logan, D; Currie, P
Abstract : The insertion of temporary pacing wires (TPW) in DGH may be carried out by general physicians and associated with high complication rates. We aimed to examine this and a protocol developed to allow safe transportation of patients to a tertiary centre where TPW was performed by cardiology specialists. Methods: Patients requiring TPW at both DGH and the tertiary centre between 2004 and 2007 were identified and their notes, biochemistry, haematology and microbiology results were reviewed to determine complication rates. X-ray screening times were noted as a marker of how challenging the procedure had been. Having presented these data, a protocol for managing and transferring these patients was devised. A further audit over a 21-month period was carried out. The number of patients transferred, complications during transfer and morbidity or mortality associated with the new protocol was assessed by case record review. The delay from TPW to permanent pacing (PPM) was calculated for all groups. Results: In the first audit period, 229 screening episodes were performed on 211 patients. Forty-three patients had TPW insertion by physicians in DGH and 168 in the tertiary centre. There was a significant difference in the infection rate as defined by rise in inflammatory markers (c-reactive protein and total white cell count), pyrexia and positive blood or lead tip culture, 15/43 (34%) in the DGH compared to 7/168(4%) in the tertiary centre (p<0.0001). Screening times were not significantly different between hospitals (p=0.893). The operator within the DGH was usually a senior house officer, and only six procedures involved the DGH cardiologists. At the tertiary centre pacing was performed or supervised by a cardiologist or a competent cardiology registrar. Under the new protocol, 49 patients were transferred to the tertiary centre over a 21-month period with three screening episodes at the DGH. Thirty-four of these transfers were as emergencies to undergo TPW. Of these 34, all except one underwent PPM prior to discharge. No patients suffered cardiac arrest prior to reaching the tertiary centre and no patients died. Screening time and infection rate remained low in the tertiary centre 2.8 min (SD 1.80) and 3/67 (4%) respectively. There was a trend to shorter delay from TPW to PPM for the DGH patients (mean 3.5 days cf 2.9 days with the new protocol (p=0.06)). There was no change in the delay for patients presenting directly to the tertiary centre. Discussion: Our data are consistent with previous studies illustrating high complication rates associated with temporary pacing. We have demonstrated the safety and efficacy of a protocol for the transfer of patients from the DGH to the tertiary centre where TPW insertion is associated with fewer infective complications .The reduction in infection rates does not appear to be related to x-ray screening time or the delay from TPW to PPM.